Thrombolytic actions of reptilase - Liao Chang-Long; Zou Qi-Jun (Acta Pharmacologica Sinica, 2016)
In thrombolytic model in vitro, reptilase (Rep, defibrase) did not show appreciable thrombolytic actions on red and white thrombi. After daily iv infusion of Rep 0.25 IU for 10 d, the time of 50% lysis of euglobulin (ELT1/2) was shortened from 9.3 +/- 0.8 to 6.7 +/- 1.0 h (P < 0.01), alteplase activity was increased from 1.9 +/- 0.7 to 3.7 +/- 0.9 IU.ml-1, and plasminogen inactivator (PI) activity reduced from 4.3 +/- 0.6 to 1.8 +/- 0.9 AU.ml-1 (all P < 0.01). The findings indicate that the thrombolytic action of Rep shown in vivo may not be from the direct action on thrombi but from the influence on alteplase and PI activity.